2009
DOI: 10.1371/journal.pone.0005279
|View full text |Cite
|
Sign up to set email alerts
|

Features of Mammalian microRNA Promoters Emerge from Polymerase II Chromatin Immunoprecipitation Data

Abstract: BackgroundMicroRNAs (miRNAs) are short, non-coding RNA regulators of protein coding genes. miRNAs play a very important role in diverse biological processes and various diseases. Many algorithms are able to predict miRNA genes and their targets, but their transcription regulation is still under investigation. It is generally believed that intragenic miRNAs (located in introns or exons of protein coding genes) are co-transcribed with their host genes and most intergenic miRNAs transcribed from their own RNA pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
211
0
9

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 263 publications
(228 citation statements)
references
References 52 publications
8
211
0
9
Order By: Relevance
“…According to the authors, the locations of transcription start sites vary from 0 to 40 kb upstream of miRNA genes. Furthermore, the transcription start sites of the miR-200b/a and miR-200c clusters have been suggested to be located 8763 and 1976 bp upstream of their respective cluster (Corcoran et al, 2009). In the present study, we showed that Smad3, when acting as a transcriptional activator, binds to a more proximal region (between À657 and À653 bp upstream) of miR-200b/a promoter (Figure 4).…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…According to the authors, the locations of transcription start sites vary from 0 to 40 kb upstream of miRNA genes. Furthermore, the transcription start sites of the miR-200b/a and miR-200c clusters have been suggested to be located 8763 and 1976 bp upstream of their respective cluster (Corcoran et al, 2009). In the present study, we showed that Smad3, when acting as a transcriptional activator, binds to a more proximal region (between À657 and À653 bp upstream) of miR-200b/a promoter (Figure 4).…”
Section: Discussionsupporting
confidence: 57%
“…In most cases, the transcriptional regulation of miRNA is not fully understood. Corcoran et al (2009) recently described putative transcription start sites in miRNA promoters identified by chromatin immunoprecipitation-on-chip analysis of RNA polymerase IIbinding sites. According to the authors, the locations of transcription start sites vary from 0 to 40 kb upstream of miRNA genes.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9] This hypothesis is supported by recent research predicting miRNA promoters by combining bioinformatic analysis of nearby upstream DNA regulatory elements (transcription start sites (TSS), conserved transcription factor-binding sites, TATA boxes, A/B boxes) and epigenetic modifications (CpG islands, histone modifications, nucleosome positioning patterns) with chromatin immunopreciptiation screens or reporter assays. [6][7][8][9][10][11] It seems that about half of the miRNAs located in introns of protein-coding genes (B60%) contain putative promoters regulating transcription independent of their host gene. 7 This is also supported by the observed discrepancy in expression of several miRNAs and their host genes.…”
Section: Genomic Organization Of the Mir-125b Clustermentioning
confidence: 97%
“…3. It includes nine loci (three from three different cell lines in [19] and one from each of the others [4,5,6,11,17,21]) of the same miRNA that are very close with respect to the large span of the genome, even though they differ much (σ ∼ 17225.6 for start TSS and σ ∼ 19656.4 for end TSS). …”
Section: The Mirt Databasementioning
confidence: 99%
“…Based on the genomic locus, miRNAs can be broadly categorized into two types -intragenic (miRNA-coding genes located within their host protein-coding genes) and intergenic (miRNA-coding genes located in-between protein-coding genes) [7]. It is highly anticipated that most of the intergenic miRNAs (inter-miRs) are transcribed independently based on their own RNA polymerase II enzyme (Pol II) promoter, while intragenic miRNAs (intra-miRs) are transcribed along with their host genes [5]. Current research interests concentrate on the transcriptional regulation of inter-miRs, as very little is known about whether their transcription is associated with those of their neighboring genes at all.…”
Section: Introductionmentioning
confidence: 99%